Enabling Environment Assessment and Baseline for Scaling Up Handwashing Programs : Vietnam - Cogswell, Lynne; Anh Thu, Le Thi (World Bank, Washington, DC, 2014)
To follow up country work supported by the Public-Private Partnership for Handwashing (PPPHW), the World Bank Water and Sanitation Program (WSP) received funding from the Bill & Melinda Gates Foundation to support projects to scale up the promotion of handwashing with soap (HWWS) in Peru, Senegal, Tanzania, and Vietnam. The major project objectives of the Handwashing Initiative are: a) inculcate the HWWS habit among millions of mothers and children in these countries, b) use a strong monitoring and evaluation (M&E) component to enhance the conceptualizing and management of such programs, and c) establish sustainable programs that will continue and expand after this four-year grant ends. Enabling environment assessments are being carried out in all four countries to assess current conditions for scalability and sustainability and to make recommendations for improving conditions that are not supportive. This report summarizes the study in Vietnam. All four county studies are following a similar methodology, developed by WSP, to examine nine dimensions of scalability/sustainability through individual and group in-depth interviews and an electronic survey in which respondents are asked to score various statements.